2010
DOI: 10.1186/1476-511x-9-85
|View full text |Cite
|
Sign up to set email alerts
|

Lipid ratios and appropriate cut off values for prediction of diabetes: a cohort of Iranian men and women

Abstract: BackgroundDyslipidemia is a risk factor for incident type 2 diabetes; however, no study has specifically assessed the lipid ratios (i.e. total cholesterol (TC)/high density lipoprotein cholesterol (HDL-C) and triglyceride (TG)/HDL-C) as predictors of diabetes. We aimed to compare the independent association between the different lipid measures with incident diabetes over a median follow up of 6.4 years in Iranian men and women.MethodThe study population consisted of 5201 non diabetic (men = 2173, women = 3028)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
80
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 39 publications
20
80
1
Order By: Relevance
“…In recent decades, non‐HDL has been highlighted as an important secondary therapeutic goal in the management of dyslipidemia 9, 10. In contrast with the well acknowledged potent role of non‐HDL in predicting cardiovascular diseases,7, 23 previous studies that focused on the association between non‐HDL and development of diabetes arrived at contrary conclusions 11, 13. Furthermore, there is only one study that investigated the utility of non‐HDL in assessing incident type 2 diabetes risk in people who are relatively insulin‐sensitive and at low risk for diabetes 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, non‐HDL has been highlighted as an important secondary therapeutic goal in the management of dyslipidemia 9, 10. In contrast with the well acknowledged potent role of non‐HDL in predicting cardiovascular diseases,7, 23 previous studies that focused on the association between non‐HDL and development of diabetes arrived at contrary conclusions 11, 13. Furthermore, there is only one study that investigated the utility of non‐HDL in assessing incident type 2 diabetes risk in people who are relatively insulin‐sensitive and at low risk for diabetes 12.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a retrospective study further validated the superior role of non‐HDL in predicting diabetes in people with normal glucose tolerance (NGT) 12. On the contrary, there is also a study that observed no solid association between non‐HDL and the development of diabetes 13. Therefore, a well‐designed prospective study with a larger sample size is still imperative to elucidate the role of non‐HDL in predicting incident diabetes for people with NGT.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently we showed that dyslipidemia is commonly associated with diabetes and CVD events among Iranian populations. 6,7 Dyslipidemia could lead to hypertension by mechanisms such as endothelial dysfunction resulting in impaired nitric oxide production, release and activity, and structural changes in large arteries following atherosclerosis. 8,9 Additionally, hypertension and dyslipidemia, as the components of metabolic syndrome may have universal mechanistic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, insulin resistance may be a cause of pathology. The TG/HDL-C ratio is also known as an acknowledged marker of insulin resistance [18][19][20]. Razani et al [21] reported that insulin resistance was an important contributor to the acceleration of atherogenesis.…”
Section: Discussionmentioning
confidence: 99%